The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1155/2021/5372090
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Allografts: Factors for and against Acceptance

Abstract: Cornea is one of the most commonly transplanted tissues worldwide. However, it is usually omitted in the field of transplantology. Transplantation of the cornea is performed to treat many ocular diseases. It restores eyesight significantly improving the quality of life. Advancements in banking of explanted corneas and progressive surgical techniques increased availability and outcomes of transplantation. Despite the vast growth in the field of transplantation laboratory testing, standards for corneal transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…As a consequence of this knowledge, corneal transplantation has become one of the most successfully performed solid organ transplantation, with a more than 90% rate of success in low-risk condition, while in high-risk setting it lowers to less than 50%[ 49 , 50 ]. Interestingly, the impressive success rate often witnessed in low-risk corneal grafts, unlike with other solid organ transplants, can be attained without relying on HLA matching or extensive systemic immune suppression[ 51 , 52 ]. Following transplantation, inflammation in the eye triggers the upregulation of proinflammatory cytokines like IL-1, IL-6, and TNF-α, as well as chemokines such as MIP-1α, MIP-1β, MIP-2, and RANTES[ 53 ].…”
Section: Advances and Insightsmentioning
confidence: 99%
“…As a consequence of this knowledge, corneal transplantation has become one of the most successfully performed solid organ transplantation, with a more than 90% rate of success in low-risk condition, while in high-risk setting it lowers to less than 50%[ 49 , 50 ]. Interestingly, the impressive success rate often witnessed in low-risk corneal grafts, unlike with other solid organ transplants, can be attained without relying on HLA matching or extensive systemic immune suppression[ 51 , 52 ]. Following transplantation, inflammation in the eye triggers the upregulation of proinflammatory cytokines like IL-1, IL-6, and TNF-α, as well as chemokines such as MIP-1α, MIP-1β, MIP-2, and RANTES[ 53 ].…”
Section: Advances and Insightsmentioning
confidence: 99%
“…It has been shown that ACAID, which is a part of immune privilege contributes to corneal allograft survival. In corneal transplantation, the donor allografts are in direct contact with the AC and induce ACAID through provoking a series of immunological responses blocking normal delayed type hypersensitivity response [1,[4][5][6] . In our method, direct contact between the host endothelium and donor is absent.…”
Section: Dear Editormentioning
confidence: 99%
“…3 Several factors have been associated with increased graft rejection risk, such as pre-existing glaucoma, lens status, Human Leucocyte Antigen mismatches, among others. 2,4,5 The incidence of rejection appears to increase strongly with three risk factors: corneal neovascularization, namely the number of affected quadrants, density, and activity of neovessels; the number of previous ipsilateral corneal grafts; and an infectious or inflammatory disease that otherwise compromises corneal immune privilege. 5 In most corneal transplants, but more so in such highrisk cases, long-term topical or systemic immunosuppression is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…2,4,5 The incidence of rejection appears to increase strongly with three risk factors: corneal neovascularization, namely the number of affected quadrants, density, and activity of neovessels; the number of previous ipsilateral corneal grafts; and an infectious or inflammatory disease that otherwise compromises corneal immune privilege. 5 In most corneal transplants, but more so in such highrisk cases, long-term topical or systemic immunosuppression is warranted. Current standard of care is based on topical corticosteroids, but its chronic use is associated with adverse effects such as increased intraocular pressure and cataract development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation